Effects of air abrasive polishing on chromium ion release from different metal self-ligating orthodontic brackets (Mustansiria Dental Journal, 2024)
Treatment with fixed orthodontic appliances compromises the oral hygiene and increases the risk of plaque related disorders and dental staining in addition to corrosion and corrosion byproduct: ions. The aims this study was assessment the effects of air polishing on Chromium ion (Cr) release from stainless steel self-ligating brackets.one hundred and sixty self-ligating stainless-steel brackets of four brands Damon® Q™ (Damon® Q™, Ormco, Orange, CA, USA), Discovery® SL 2.0 (Dentaraum, Ispringen, Germany), Leone® F1000 (SLB; F1000, Leone SpA, Sesto Florentino, Florentino, Italy) and Lotus Plus® (Lotus plus, Orthotechnology co., Brazil) were exposed to different time of air abrasion polishing (0, 5, 10, 20 seconds) then immersed in artificial saliva with pH value 6.75 and incubated at 37°C for 28 days. Cr ion release was assessed using atomic absorption spectrophotometer at 7, 14 and 28 days and accumulative effect was calculated. Scanning electron microscope (SEM) were used to assess the surface changes and microtopography after polishing for randomly selected sample.  Analysis of variance test (ANOVA), and Tukey’s (HSD) test were used to identify the significant difference among the studied groups where the level of significance set as P ≤ 0.05.The results revealed that all brands showed significant increase in Cr ion release concomitant with an increase in the polishing time. Damon® Q™ show the greatest amount of Cr ion releaseConclusion: The air polishing procedure enhanced the amount of Cr ion release to a subtoxic level and could be used in adult patients using 5 sec. recommended time of polishing with prolonged intervals between the visits.